Sleep Disturbances in Autoimmune Neurologic Diseases: Manifestation and Pathophysiology - Yin, Dou; Chen, Sheng; Liu, Jun (Frontiers in Neuroscience, 2021)
Autoimmune neurologic diseases are a new category of immune-mediated disease and demonstrates a widely variable spectrum of clinical manifestations. Recently, sleep disturbances were reported in patients with autoimmune neurologic diseases and have an immense negative impact on quality of life. Excessive daytime sleep, rapid eye movement sleep behaviour disorder and narcolepsy are the most frequent sleep disorders associated with autoimmune neurologic diseases. Sleep disturbances might be the initial symptoms of disease or persist throughout the whole course of disease. In this paper, we will review sleep disturbances in different autoimmune neurologic diseases and the potential pathophysiological mechanisms.